Effect of chronic alcohol consumption on myocardial apoptosis in the rat model of isoproterenol-induced myocardial injury and investigation on the cardioprotective role of calpain inhibitor 1 - Oglakci-Ilhan, Aysegul; Kusat-Ol, Kevser; Uzuner, Kubilay; Uysal, Onur; Sogut, Ibrahim; Yucel, Ferruh; Kanbak, Gungor (TAYLOR & FRANCIS LTD, 2022)
We investigated the presence of myocardial apoptosis on isoproterenol (ISO)-induced myocardial injury (MI) after long-term high dose alcohol consumption and examined the antiapoptotic role of calpain inhibitor 1. Male Wistar Albino rats (n = 108) were divided into six groups: Control, alcohol (ethanol was given during 30 days for chronic alcohol consumption), MI (150 mg/kg ISO injection at last two days of alcohol consumption), alcohol + MI, alcohol + MI + calpain inhibitor 1 (10 mg/kg inhibitor was injected at 15 min before ISO injections) and Dimethyl Sulfoxide (DMSO) groups. Biochemical, histological, and morphometric methods determined apoptosis levels in the heart tissue of rats. Cytochrome c, caspase 3, and calpain levels were significantly high in alcohol, MI, and alcohol + MI groups. In contrast, mitochondrial cardiolipin content was found to be low in alcohol, MI, and alcohol + MI groups. These parameters were close to the control group in the therapy group. Histological and morphometric data have supported biochemical results. As a result of our biochemical data, myocardial apoptosis was seen in the alcohol, MI, and especially alcohol after MI groups. Calpain inhibitor 1 reduced apoptotic cell death and prevented myocardial tissue injury in these groups. The efficiency of calpain inhibitor was very marked in MI after long-term high dose alcohol consumption.
Keywords: Alcohol; apoptosis; calpain inhibitor; myocardial injury; rat; REDUCES INFARCT SIZE; CARDIOLIPIN; MITOCHONDRIA; ETHANOL; HEART; TOXICITY; ISCHEMIA; PROTECTS; Chemistry; Pharmacology & Pharmacy; Toxicology